Strengthening of heat-damaged steel fiber-reinforced concrete using CFRP composites: Experimental study and analytical modeling. (August 2021) - Nematzadeh, Mahdi; Hasan-Nattaj, Farid; Gholampour, Aliakbar; Sabetifar, Hassan; Ngo, Tuan D.
Abstract: Retrofitting concrete with fiber-reinforced polymer (FRP) wrap has been considered as an effective method to compensate for the loss of the compressive strength of the concrete at an elevated temperature. This paper presents a study on the axial compressive behavior of heat-damaged steel fiber-reinforced concrete strengthened with carbon FRP (CFRP) wraps. To this effect, steel fibers were added to two concrete mixtures with volume fractions of 0.5% and 1%. The effect of full and partial wrapping with CFRP composites on the compressive behavior of the heated concrete was examined. A stress–strain model was also proposed to predict the behavior of CFRP-confined post heated steel fiber-reinforced concrete. It was found that heated concrete wrapped with CFRP layers exhibits a higher compressive strength, peak axial strain, maximum volumetric strain, toughness and relative energy absorption than that of unwrapped concrete. The results also showed that the exposure of concrete to the heat leads to a slight decrease in the ascending and descending slopes of the axial stress–strain relationship. The comparison between the model predictions and experimental results revealed that the proposed model accurately predicts the axial stress-axial strain and axial stress-lateral strain of the heated concrete. These results are promising and demonstrate the benefits of full and partial FRP wrapping in the development of high-performance structural members subjected to an elevated temperature.